A critical review on intelligent and active packaging in the food industry: Research and development. (March 2021) - Soltani Firouz, Mahmoud; Mohi-Alden, Khaled; Omid, Mahmoud
Graphical abstract: Highlights: Recent developments on AP and IP are reviewed as the emerging technologies. The need to quality and safety led to emergence intelligent and active packaging methods. Quality and safety promotion and increasing shelf-life of food are advantages of AP. Quality monitoring and helping to control of storage conditions are benefits of IP. Further studies will make AP and IP promising tools in providing high quality food. Abstract: The emergence of many new food products on the market with need of consumers to constantly monitor their quality until consuming, in addition to the necessity for reducing food corruption during preservation time, have led to the development of some modern packaging technologies such as intelligent packaging (IP) and active packaging (AP). The benefits of IP are detecting defects, quality monitoring and tracking the packaged food products to control the storage conditions from the production stage to the consumption stage by using various sensors and indicators such as time-temperature indicators (TTIs), gas indicators, humidity sensors, optical, calorimetric and electrochemical biosensors. While, AP helps to increase the shelf-life of products by using absorbing and diffusion systems for various materials like carbon dioxide, oxygen, and ethanol. However, there are some important issues over these emerging technologies including cost, marketability, consumer acceptance, safety and organoleptic quality of the food and emphatically environmental safety concerns. Therefore, future researches should be conducted to solve these problems and to prompt applications of IP and AP in the food industry. This paper reviews the latest innovations in these advanced packaging technologies and their applications in food industry. The IP systems namely indicators, barcoding techniques, radio frequency identification systems, sensors and biosensor are reviewed and then the latest innovations in AP methods including scavengers, diffusion systems and antimicrobial packaging are reviewed in detail.